Integration of Ecotheology Literacy Games Through Deep Learning to Increase Environmental Awareness for Students in IPAS Learning - Fitria Martanti; Maskur Maskur (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2025)
This study aims to analyze the use of ecotheology literacy games through in-depth learning to increase environmental awareness among students in science subjects at Medani State Elementary School. The method used in this study is qualitative, with a case study design. Data collection was conducted through participatory observation, in-depth interviews, and document analysis. The results of the study show that the use of ecotheology literacy games can increase student involvement, strengthen understanding of ecological concepts, and encourage the internalization of environmental care values. Of the 16 students involved, as many as 15 demonstrated excellent ecological awareness, as evidenced by behavioral changes, critical reflections, and concrete actions taken to maintain cleanliness and preserve the school environment. The deep learning approach helps students connect in-game experiences to everyday life, fostering more meaningful ecological understanding and attitudes. Thus, the integration of ecotheology literacy games into social studies learning has proven to be an innovative pedagogical strategy that is both relevant and appropriate for strengthening environmental education from an early age.